Physicochemical Characterization of Chitosan-Multiwalled Carbon Nanotubes Hybrid Material for Ofloxacin Delivery - Khudair, Zainab Jasim; Kadam, Zeina Mohammad (Universitas Gadjah Mada, 2024)
The present study involved the synthesis of a bioactive composite material using chitosan (CS) and multi-walled carbon nanotubes (MWCNTs) through the free radical polymerization method. The resulting composite material was comprehensively characterized using various experimental techniques, such as Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The quantification of the swelling behavior involved the measurement of changes in the weight of the sample as a function of the time it was immersed in an aqueous buffered solution. The findings indicated that the maximum drug-loading rate of ofloxacin medication (OFL) was 86%. Moreover, the pH sensitivity of the poly acrylic acid grafting multi-walled carbon nanotubes p(CS-co-AA)/MWCNTs nanocomposite facilitated the substantial release of a significant quantity of medication in aqueous buffered solution at a pH of 1.2. The average rate of drug release was measured to be 76% after 72 h duration. On the other hand, the release of the drug at pH 5 and 7.4 was 42% and 32%, respectively. According to the reported findings, the p(CS-co-AA)/MWCNTs carrier has a favorable capacity to control the release of the OFL drug into the intended medium while reducing potential negative effects.